ANALYSIS OF THE ABSORPTION OF LABOR ON SMALL INDUSTRIES IN TRENGGALEK (Case Study On Tempe Keripik Enterprises At Bendorejo In Trenggalek) - Wibowo, Sukma Patria Arianto (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aimed to determine wether the variables of capital, wage, sales turnover and business hours affect on labor absorption of small industries and to determine what the most dominant variable affects labor absorption on small industries inTrenggalek. The case study was conducted on small industries tempe keripik at Bendorejo Village in Trenggalek as many as 40 entreprenuers that showed as study of sample. Technique of data collection was conducted by distributing questionaires. The method of analysis use the Hypthesis Test, Multiple Regression Test, R Square Test, and also Dominant Test. In this study can be conluded that the most dominant variable that affect on labor absorption (Y) is capital (X). Then can be known that in partialy variables that affect significant on labor absorption (Y) are capital (X1), wages (X2) and business hours (X4) while sales turnover (X) does not affect on labor absorption (Y) of small industries tempe keripik. Furthermore, in simultaneously ofcapital (X1), wages (X2), sales turnover (Y33) and business hours (X) affect significant on labor absorption (Y) of small industries tempe keripik at Bendorejo Village in Trenggalek.Keyword: The Capital, Wages, Sales Turnover, Business hours, Employment